Daniel Alcides Carrion and his contribution to peruvian medicine cultural imaginary - Murillo, Juan (2002)
This study analizes Daniel Alcides Carrion role as a cultural hero and central element of Peruvian medical tradition. We verify the meaning of the elaboration process of Carrions experiment in a political struggle and national reconstruction scenery that converges with the beginning of the century aristocratic elite positivism. Social recomposition of medical institutions and the emergent fraction entrance to the Faculty of Medicine makes end of the XIX century-Carrions created image to become a neutral icon at the present time, amenable to absolute reivindication by all sectors as it is deeply rooted in the past with no current presence. A cultural imaginary analysis of Peruvian Medical School development (1886-1956) is done, as during this period San Fernando produced the countrys largest and best quality medical knowledge. We conclude that confluence of local medical imaginary elements -Carrion as endowment myth, emergent resistance, academical, ethical and moral rebuilding, and restoration project- made possible Peruvian Medical School appearance; and consequently the development and social genuineness of Peruvian medicine, rep- resenting the foundation of a new medical culture within refoundation and building of a new country.